Crevasse-Squeeze Ridges in Trygghamna, Svalbard - Daniel Ben-Yehoshua 1989- (2017)
Glacial geologists have been discussing the processes behind the formation of Crevasse-Squeeze Ridges (CSRs) since they were first described from the forefield of Eyjabakkajökull, Iceland, in the mid 1980s. To date, CSRs are, together with concertina eskers, the only landforms that have been described exclusively in the forefields of surge-type glaciers. However, much remains to be learned about these ridges and their glaciological significance. This thesis describes geometrical and transverse sediment ridges appearing after surge events of polythermal glaciers in Trygghamna, West Svalbard. In order to understand the geomorphic context of these landforms, detailed maps were produced via remote sensing and field mapping. These maps illustrate striking differences in CSR configurations found in marine and terrestrial settings. Historical images from 1936 were used to compare the geometry of former glacier surface structures with mapped CSRs. Furthermore, analysis of CSRs in cross-sections sheds light on the architecture and sedimentology of these formations. Results from Trygghamna suggest that basal till was squeezed into basal crevasses during a surge and transported englacially before deposition. Mapped landform assemblages suggest that at least two glaciers in Trygghamna have surged in the past. Additionally, CSRs are observed in an area of a former glacial shear-zone between a surge-type and a non-surge-type glacier. A conceptual model for the formation and preservation of CSRs in Trygghamna is proposed. The results of this thesis not only further contemporary understanding of CSRs in Trygghamna, but may also apply to large-scale glacial or ice stream settings.